2017
DOI: 10.5603/oj.2017.0012
|View full text |Cite
|
Sign up to set email alerts
|

Correction of astigmatism with toric intraocular lenses

Abstract: The purpose of this article is to explain how astigmatism can be eliminated during cataract surgery by using toric intraocular lenses (IOLs). The toric IOL calculation is analysed as well as the various types of toric IOLs. The toric IOL implantation technique is also explained and thoroughly analysed. Moreover, the possibility of residual astigmatism after the surgery is discussed as well as the reasons for this and how to deal with it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…U haptik typu plate dochází během dvou týdnů k celkovému a symetrickému spojení vaku, což vede k nižší rotaci v pozdějším pooperačním období. U čoček designu loop haptik dochází k asymetrické fúzi ve směru hodinových ručiček, pozdní rotace čočky je běžnější [21]. K pooperační rotaci TIOL více než 10° dochází nejčastěji do 10 dnů od operace katarakty [4].…”
Section: Diskuzeunclassified
“…U haptik typu plate dochází během dvou týdnů k celkovému a symetrickému spojení vaku, což vede k nižší rotaci v pozdějším pooperačním období. U čoček designu loop haptik dochází k asymetrické fúzi ve směru hodinových ručiček, pozdní rotace čočky je běžnější [21]. K pooperační rotaci TIOL více než 10° dochází nejčastěji do 10 dnů od operace katarakty [4].…”
Section: Diskuzeunclassified
“…Previous studies have shown that the toric lens undergoes the highest rotation between 1 hour and 10 days after surgery [4]. The principal factors leading to rotational instability of toric lenses have been identified as intraoperative hypotonia, the presence of residual viscoelastic material posterior and/or anterior to the IOL, and lens bag-related factors such as capsular bag contraction, phimosis, shrinkage, as well as capsular bag diameter and capsulorhexis size [3,4]. However, other factors such as axial length (AL) and IOL-related factors such as its design/ material, axis IOL alignment, and IOL's haptic diameter have also been proposed [9].…”
Section: Rotational Stabilitymentioning
confidence: 99%
“…Substantial rotation of the toric lens can be resolved by repositioning the previously implanted lens before complete fusion between the artificial lens and the lens bag. If repositioning is impossible, residual astigmatism can be corrected non-invasively with spectacles or surgically by implanting a second toric lens into the ciliary sulcus or performing refractive corneal surgery [3].…”
Section: Rotational Stabilitymentioning
confidence: 99%
See 1 more Smart Citation